HOMILADOR AYOLLARNING SOG‘LOM OVQATLANISHIDA AYRIM VITAMINLARNING O‘RNI - Buranova, Gulnoza; Buranov , Botir (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
HOMILADOR AYOLLARNING SOG‘LOM OVQATLANISHIDA AYRIM VITAMINLARNING O‘RNI